A novel role for Atmin as a transcription factor controlling ciliogenesis - Stevens, J (2011)
Cilia are cellular organelles involved in processing components of the hedgehog (hh) signalling pathway and determining left-right (L-R) axis formation in the embryo. An embryonic lethal mouse mutant, called gasping 6 (gpg6), was identified that demonstrated morphological and molecular defects associated with L-R development and hh signalling. gpg6 mutant embryos also demonstrate abnormally short cilia, which was hypothesised to be the primary morphological defect in gpg6 mutants. The underlying genetic lesion in gpg6 is a mutation in the DNA repair gene Atmin. The base pair change results in an amino acid substitution in a critical residue in the third zinc finger of Atmin. The consequence of this change is the failure to activate transcriptional targets of Atmin. This raised the possibility that previously unidentified Atmin target genes are important for ciliogenesis. Consistent with this hypothesis, Dynein light chain-LC8 (Dynll1) is downregulated in gpg6 mutants. LC8 (a homolog of mouse Dynll1) is required, in the single cell eukaryotic organism Chlamydomonas, for retrograde intraflagellar transport (IFT), a process crucial for ciliogenesis. These data led to the following hypothesis: Atmin activates expression of Dynll1, which functions in retrograde IFT to enable normal ciliogenesis. Knockdown of Atmin in a ciliated kidney cell line resulted in abnormally short cilia. Thus, Atmin functions in ciliogenesis. Investigation of gpg6 has therefore identified a novel role for Atmin in ciliogenesis and has added to the growing knowledge of genes that control cilia formation and embryonic development.